2010
DOI: 10.1177/1059840510364844
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Principles as a Guide in Implementing Policies for the Management of Food Allergies in Schools

Abstract: Food allergy in children is a growing public health problem that carries a significant risk of anaphylaxis such that schools and child care facilities have enacted emergency preparedness policies for anaphylaxis and methods to prevent the inadvertent consumption of allergens. However, studies indicate that many facilities are poorly prepared to handle the advent of anaphylaxis and policies for the prevention of allergen exposure are missing essential components. Furthermore, certain policies are inappropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Previous studies determined that only 25% to 28% of students who have asthma have a written plan on file with their school. 19,20 In addition, although food allergy management plans are widely recommended as a best practice for schools, 8,[21][22][23] their use in US school districts has been inconsistent. For example, a Mississippi study found that statewide variation in the use of school health management plans ranged from 0% to 37% among food allergic students.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies determined that only 25% to 28% of students who have asthma have a written plan on file with their school. 19,20 In addition, although food allergy management plans are widely recommended as a best practice for schools, 8,[21][22][23] their use in US school districts has been inconsistent. For example, a Mississippi study found that statewide variation in the use of school health management plans ranged from 0% to 37% among food allergic students.…”
Section: Discussionmentioning
confidence: 99%
“…The reality is that many facilities are poorly prepared to protect students. Essential components of policies for the prevention of food allergen exposure are missing (1,45), teachers have poor knowledge of anaphylaxis triggers, symptoms, and AAIs (16,(46)(47)(48), and PEMPs are not currently consistently provided for the majority of students with FA (16).…”
Section: Schoolmentioning
confidence: 99%
“…There may be significant barriers to be overcome in this regard as 'education' and 'health' are often governed by different municipal governmental bodies. Therefore, fostering a cooperative partnership between doctors, community nurses, dietitians, parents, and the school community is essential (48).…”
Section: Schoolmentioning
confidence: 99%
“…[122][123][124] Also, the necessity to consider early the ethical aspects of possible policy to be proposed for implementation after research in allergy becomes an imperative. 125 The importance of all these ethical dimensions is recognized in the MeDALL project, and such topics are addressed in specific tasks that go beyond a classical ethical management of the project.…”
Section: Ethical Aspects Of the New Approaches In Medallmentioning
confidence: 99%